A4_18 Your Guests Are Thirsty - Coxon, John; Barker, Joshua; Conlon, Thomas (Physics Special Topics, 2011)
In RollerCoaster Tycoon 2 it is possible to build stalls and set the prices for drinks and other consumables. This paper runs a simulation in one scenario to set multiple prices for drinks and then examine what the effect that this has on profits is over a four month period. It is found that the optimum price for drinks lies between Â£2.10 and Â£2.40.